Using multi-criteria decision analysis to describe stakeholder preferences for new quality improvement initiatives that could optimise prescribing in England - Khanal, Saval; Schmidtke, Kelly Ann; Talat, Usman; Turner, Alice M.; Vlaev, Ivo (Frontiers in Health Services, 2023)
Background. Hospital decision-makers have limited resources to implement quality improvement projects. To decide which interventions to take forward, trade-offs must be considered that inevitably turn on stakeholder preferences. The multi-criteria decision analysis (MCDA) approach could make this decision process more transparent. Method. An MCDA was conducted to rank-order four types of interventions that could optimise medication use in England’s National Healthcare System (NHS) hospitals, including Computerised Interface, Built Environment, Written Communication, and Face-to-Face Interactions. Initially, a core group of quality improvers (N = 10) was convened to determine criteria that could influence which interventions are taken forward according to the Consolidated Framework for Implementation Research. Next, to determine preference weightings, a preference survey was conducted with a diverse group of quality improvers (N = 356) according to the Potentially All Pairwise Ranking of All Possible Alternatives method. Then, rank orders of four intervention types were calculated according to models with criteria unweighted and weighted according to participant preferences. Results. The most important criteria influencing what interventions were preferred was whether they addressed ‘patient needs’ and their financial ‘cost’. In both the unweighted and weighted models, the top-ranked intervention type was Computerised Interface followed by Built Environment. In the unweighted model, Written Communication and Face-to-Face intervention types were ranked similarly, while in the weighted model, the Face-to-Face type was ranked lower. Conclusions. An MCDA was conducted to rank order intervention types that stand to increase medication optimisation across hospitals in England. The top-ranked intervention type was the Computerised Interface. This finding does not imply Computerised Interface interventions are the most effective interventions but suggest that successfully implementing lower-ranked interventions may require more conversations to appreciate stakeholder concerns.